Method for preparing alpha-type high-strength gypsum from powdery attapulgite associated gypsum

Through crushing, sieving and constant temperature dehydration treatment of concave and convex rock companion gypsum, combined with the use of crystallization agent and stimulating agent, high-strength α-type gypsum was successfully prepared, solving the problems of complex and high cost of gypsum preparation in the prior art, and achieving efficient and low-cost gypsum preparation.

CN119528467APending Publication Date: 2025-02-28XIANYANG NON-METALLIC MINE RES & DESIGN INST CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411714345.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-02-28

Smart Images

  • Figure BDA0005156562480000071
    Figure BDA0005156562480000071
Patent Text Reader

Abstract

The invention discloses a method for preparing alpha-type high-strength gypsum from powdery attapulgite associated gypsum, and belongs to the technical field of building materials, and the method comprises the following steps: crushing the attapulgite associated gypsum, sieving, re-crushing oversize products until all the oversize products are sieved, and then carrying out constant-temperature dehydration on undersize products to obtain the powdery associated gypsum; the method comprises the following steps: adding powdery associated gypsum into a mixer, adding water, spraying a crystal modifier to the powdery associated gypsum while stirring, adjusting the pH value after the crystal modifier is sprayed, adding an exciting agent, and continuously stirring uniformly; and dehydrating and drying the crystal-transformed material, and grinding to obtain the alpha-type high-strength gypsum. The method has the advantages of simple process, low equipment investment, high production efficiency, low production cost, stable quality, high productivity, good product performance and strong adaptability to raw materials. The alpha-type high-strength gypsum is prepared by a powder autoclaving method, so that a way is provided for high-valued and large-scale utilization of associated gypsum, and beneficial exploration is provided for upgrading and transformation of the gypsum industry.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building materials, in particular to a method for preparing alpha-type high-strength gypsum by using powdered attapulgite-associated gypsum. Background Art

[0002] Gypsum is a truly green, low-carbon, environmentally friendly cementitious material that can be recycled. It is one of the three major inorganic cementitious materials along with lime and cement and has a long history of application. The earliest humans accidentally discovered that gypsum had gelling properties after heating it, and then processed it into a cementitious material for use in the construction industry. Ancient Chinese medicine used gypsum as one of the medicinal materials. At present, according to different uses, gypsum can be processed into high-strength gypsum, building gypsum, gypsum whiskers and other products, which are used in precision casting, medicine, ceramic molds, rubber, papermaking and other fields. It can be seen that gypsum has a wide range of applications and has an important economic and social status.

[0003] At present, the raw materials used in the production of high-strength gypsum are mainly high-purity gypsum, and the production processes mainly include traditional autoclave, pressurized hydrothermal method and normal pressure solution method. Traditional autoclave is the method currently commonly used in China. Generally, block gypsum is used as raw material, which is placed in a stationary autoclave for heating, dehydrated, crystallized, dried, and ground into products. Its production cycle is as long as 18h to 20h, with low production efficiency and poor output quality. The general compressive strength is 25MPa to 30MPa. The pressurized hydrothermal method originated in Europe. It processes block gypsum into powder. It can also directly use desulfurized gypsum and add it to a solution mixed with an admixture for autoclaving. After dehydration, crystallization, drying, and grinding, it becomes a product. Its process is complex, the equipment investment is large, the wastewater treatment volume is large, and the production cost is high, but the product quality is good, and the compressive strength can reach 60MPa. The normal pressure solution method is to add gypsum powder to hydrochloric acid solution and carry out dehydration and crystallization processes under normal pressure. Due to the high corrosiveness of hydrochloric acid solution to equipment and poor product stability, very few industrial production methods have been achieved.

[0004] The associated gypsum has the characteristics of high attached water content and fine particles, and it is difficult to prepare high-strength gypsum. The conventional method of using semi-raw gypsum to prepare high-strength gypsum is to directly use block gypsum for preparation, and the conventional preparation of high-strength gypsum requires the addition of a large amount of crystallization agent.

[0005] Therefore, providing a method for preparing α-type high-strength gypsum using powdered attapulgite-associated gypsum is a technical problem that those skilled in the art urgently need to solve. Summary of the invention

[0006] In view of this, the present invention provides a method for preparing α-type high-strength gypsum by using powdered attapulgite-associated gypsum.

[0007] To achieve the above object, the present invention adopts the following technical solution:

[0008] A method for preparing α-type high-strength gypsum from powdered attapulgite-associated gypsum comprises the following steps:

[0009] (1) crushing the attapulgite-associated gypsum and then sieving it, crushing the material on the sieve again until it is completely sieved, and then dehydrating the material under the sieve at a constant temperature to obtain powdered associated gypsum;

[0010] (2) adding powdered associated gypsum to a mixer and adding water, then spraying a crystal-changing agent on the powdered associated gypsum while stirring, adjusting the pH to 4-8 after spraying the crystal-changing agent, adding an activator and continuing to stir evenly;

[0011] (3) The crystallized material is dehydrated and dried, and then mixed with silicon dioxide and ground to obtain α-type high-strength gypsum.

[0012] Furthermore, the attapulgite associated gypsum in step (1) is crushed and sieved to a particle size of 0.2-2 mm.

[0013] Furthermore, the constant temperature dehydration temperature in step (1) is 140-160° C., the dehydration time is 60-150 min, and the crystal water content of the powdered associated gypsum after dehydration is 3-10%.

[0014] The beneficial effect of adopting the above further scheme is that through precise control of the particle size of crushing and screening, as well as constant temperature dehydration and fine regulation of the crystal water content after dehydration, the uniformity and stability of the raw materials are ensured, laying a solid foundation for the subsequent preparation of high-quality α-type high-strength gypsum.

[0015] Further, in step (2), the crystal-transforming agent in step (2) is a composite crystal-transforming agent of aluminum sulfate, ethylenediaminetetraacetic acid and sodium citrate; the mass ratio of aluminum sulfate, ethylenediaminetetraacetic acid and sodium citrate in the crystal-transforming agent is 1:1-1.5:1-1.5;

[0016] The activator is a mixture of sodium silicate and triisoalkanolamine, and the mass ratio of sodium silicate to triisoalkanolamine in the activator is 1:0.2-0.35.

[0017] Furthermore, the amount of water added in step (2) is 10-20% of the mass of the powdered associated gypsum;

[0018] The dosage of the crystallization agent is 0.2-0.6% of the mass of the powdered associated gypsum;

[0019] The dosage of the activator is 0.5-1% of the mass of the powdered associated gypsum.

[0020] The beneficial effect of adopting the above further scheme is that the use of composite crystal-changing agents such as aluminum sulfate and sodium citrate, combined with the use of activators, effectively promotes the transformation of gypsum crystal forms, increases the proportion of α-type gypsum, optimizes the microstructure of gypsum, and significantly improves the strength and durability of gypsum. At the same time, the use of the above composite crystal-changing agent can promote the formation of high-strength gypsum seeds, thereby reducing the use of crystal-changing agents and further improving the strength of gypsum.

[0021] Furthermore, saturated water vapor is introduced when the crystal-changing agent is sprayed in step (2).

[0022] Furthermore, saturated steam is introduced into the reactor until the pressure inside the reactor reaches 0.5-0.8 MPa.

[0023] The beneficial effect of adopting the above further scheme is that in the present invention, saturated water vapor penetrates into the material through the steam distribution pipeline, heats and stabilizes the material and provides a saturated water vapor medium of a certain pressure, and the gypsum crystallizes under the action of pressure, saturated water vapor medium, temperature, and crystal-transforming agent to form a mixed crystal with a polymorphic combination of short columnar crystals and a large and small crystal gradation, thereby further improving the strength of the gypsum.

[0024] Furthermore, the stirring rate in step (2) is 150-250 r / min, and the stirring time each time is 2-4 h.

[0025] Furthermore, the dehydration and drying temperature in step (3) is 140-160° C., the dehydration and drying time is 60-150 min, and the crystal water content of the powder after dehydration and drying is 5-7%.

[0026] Furthermore, in step (3), the mass ratio of the crystallized material to silicon dioxide is 1:0.05-0.15.

[0027] The beneficial effects of the present invention are:

[0028] The present invention is aimed at the area where the applicant is located, and creatively uses powdered attapulgite-associated gypsum to prepare α-type high-strength gypsum. The method of using powdered attapulgite-associated gypsum to prepare high-strength gypsum in the present invention has a simpler process, less equipment investment, high production efficiency, low production cost, stable quality, large production capacity, good product performance, and strong adaptability to raw materials. The powder autoclave method is used to prepare α-type high-strength gypsum, which provides a way to high-value and large-scale utilization of associated gypsum, and is a beneficial exploration for the upgrading and transformation of the gypsum industry. The present invention is suitable for preparing α-type high-strength gypsum from natural gypsum, and the drying compressive strength is at least 60MPa. The present invention realizes the effective utilization of attapulgite-associated gypsum through specific process steps, and converts it into high-quality α-type high-strength gypsum, which not only broadens the application field of attapulgite-associated gypsum, but also increases the added value of resources, which is in line with the concept of sustainable development. DETAILED DESCRIPTION

[0029] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] Example 1

[0031] A method for preparing α-type high-strength gypsum using powdered attapulgite-associated gypsum:

[0032] (1) grinding attapulgite associated gypsum with a calcium sulfate content of more than 85% and passing it through a 0.2 mm sieve, grinding the sieved material again until it is completely sieved, and then dehydrating the sieved material at a constant temperature of 140° C. for 150 minutes to obtain powdered associated gypsum;

[0033] (2) Add powdered associated gypsum to a mixer and add water, then stir at 250 r / min, spray a crystallization agent on the powdered associated gypsum and introduce saturated water vapor to a pressure of 0.8 MPa, adjust the pH to 8 after spraying the crystallization agent, add an activator and continue stirring at 250 r / min for 4 hours; wherein the mass ratio of aluminum sulfate, ethylenediaminetetraacetic acid and sodium citrate in the crystallization agent is 1:1.2:1.2; the mass ratio of sodium silicate and triisoalkanolamine in the activator is 1:0.2-0.35; the amount of water added is 20% of the mass of the powdered associated gypsum; the amount of the crystallization agent is 0.6% of the mass of the powdered associated gypsum; the amount of the activator is 0.5% of the mass of the powdered associated gypsum;

[0034] (3) The crystallized material is dehydrated and dried at 140° C. for 150 min, and then mixed and ground with 0.15 times the amount of silicon dioxide to obtain α-type high-strength gypsum.

[0035] Example 2

[0036] A method for preparing α-type high-strength gypsum using powdered attapulgite-associated gypsum:

[0037] (1) grinding attapulgite associated gypsum having a calcium sulfate content of more than 85% and passing it through a 2 mm sieve, grinding the sieved material again until it is completely sieved, and then dehydrating the sieved material at a constant temperature of 160° C. for 60 minutes to obtain powdered associated gypsum;

[0038] (2) Add powdered associated gypsum to a mixer and add water, then stir at 150 r / min, spray a crystallization agent on the powdered associated gypsum and introduce saturated water vapor to a pressure of 0.5 MPa, adjust the pH to 4 after spraying the crystallization agent, add an activator and continue stirring at 150 r / min for 2 hours; wherein the mass ratio of aluminum sulfate, ethylenediaminetetraacetic acid and sodium citrate in the crystallization agent is 1:1.3:1.4; the mass ratio of sodium silicate and triisoalkanolamine in the activator is 1:0.2-0.35; the amount of water added is 10% of the mass of the powdered associated gypsum; the amount of the crystallization agent is 0.2% of the mass of the powdered associated gypsum; the amount of the activator is 1% of the mass of the powdered associated gypsum;

[0039] (3) The crystallized material is dehydrated and dried at 160° C. for 60 min, and then mixed and ground with 0.05 times the amount of silicon dioxide to obtain α-type high-strength gypsum.

[0040] Example 3

[0041] A method for preparing α-type high-strength gypsum using powdered attapulgite-associated gypsum:

[0042] (1) grinding attapulgite associated gypsum with a calcium sulfate content of more than 85% and passing it through a 2 mm sieve, grinding the sieved material again until it is completely sieved, and then dehydrating the sieved material at a constant temperature of 150° C. for 60 minutes to obtain powdered associated gypsum;

[0043] (2) Add powdered associated gypsum to a mixer and add water, then stir at 175 r / min, spray a crystallization agent on the powdered associated gypsum and introduce saturated water vapor to a pressure of 0.6 MPa, adjust the pH to 6 after spraying the crystallization agent, add an activator and continue stirring at 175 r / min for 3 hours; wherein the mass ratio of aluminum sulfate, ethylenediaminetetraacetic acid and sodium citrate in the crystallization agent is 1:1.5:1; the mass ratio of sodium silicate and triisoalkanolamine in the activator is 1:0.32; the amount of water added is 15% of the mass of the powdered associated gypsum; the amount of the crystallization agent is 0.3% of the mass of the powdered associated gypsum; the amount of the activator is 0.7% of the mass of the powdered associated gypsum;

[0044] (3) The crystallized material is dehydrated and dried at 150° C. for 60 min, and then mixed and ground with 0.06 times the amount of silicon dioxide to obtain α-type high-strength gypsum.

[0045] Example 4

[0046] A method for preparing α-type high-strength gypsum using powdered attapulgite-associated gypsum:

[0047] (1) pulverizing attapulgite associated gypsum having a calcium sulfate content of more than 85% and then passing it through a 2 mm sieve, re-pulverizing the sieved material until all of it passes through the sieve, and then dehydrating the sieved material at a constant temperature of 140° C. for 120 min to obtain powdered associated gypsum;

[0048] (2) Add powdered associated gypsum to a mixer and add water, then stir at 200 r / min, spray a crystallization agent on the powdered associated gypsum and introduce saturated water vapor to a pressure of 0.5 MPa. After spraying the crystallization agent, adjust the pH to 6, add an activator and continue stirring at 200 r / min for 4 hours; wherein the mass ratio of aluminum sulfate, ethylenediaminetetraacetic acid and sodium citrate in the crystallization agent is 1:1.3:1.5; the mass ratio of sodium silicate and triisoalkanolamine in the activator is 1:0.25; the amount of water added is 15% of the mass of the powdered associated gypsum; the amount of the crystallization agent is 0.5% of the mass of the powdered associated gypsum; the amount of the activator is 0.5% of the mass of the powdered associated gypsum;

[0049] (3) The crystallized material is dehydrated and dried at 150° C. for 60 min, and then mixed and ground with 0.08 times the amount of silicon dioxide to obtain α-type high-strength gypsum.

[0050] Comparative Example 1

[0051] The solution is the same as that of Example 4, except that sodium dodecylbenzene sulfonate is used as the crystal-transforming agent.

[0052] Comparative Example 2

[0053] The scheme is the same as that of Example 4, except that no activator is added.

[0054] Comparative Example 3

[0055] The scheme is the same as that of Example 4, except that no silicon dioxide is added.

[0056] Comparative Example 4

[0057] The method is the same as that of Example 4, except that block-shaped associated gypsum is directly used for crystal transformation and subsequent treatment.

[0058] Test example

[0059] According to the schemes of Examples 1-4 and Comparative Examples 1-3, α high-strength gypsum was prepared using attapulgite-associated gypsum, and the results are shown in Table 1

[0060]

[0061] The experimental results show that the water demand of the high-strength gypsum prepared by the method of the present invention at the standard consistency is significantly controlled below 0.36, which is much lower than the standard consistency value of the comparative example, indicating that the present method has achieved remarkable results in optimizing the hydration characteristics and working performance of gypsum materials. The reduction in water demand not only means that water resources can be used more effectively in the production process, but also improves the molding efficiency and final quality of gypsum products. In addition, the final setting time of the gypsum samples prepared by the method of the present invention is consistently maintained at about 10 minutes, which is particularly important for occasions requiring rapid curing applications, such as rapid repair materials or mold manufacturing in the construction industry. In contrast, the gypsum prepared by the comparative method generally has a longer setting time. The method of the present invention can not only effectively convert the associated gypsum into α-type high-strength gypsum, but also the drying compressive strength of the obtained product generally exceeds 60MPa, which is a strength index much higher than that of ordinary high-strength gypsum materials, sufficient to meet the requirements of high-strength structural materials, and broaden the application field of gypsum materials.

[0062] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. A method for preparing α-type high-strength gypsum using powdered attapulgite-associated gypsum, characterized in that: The following steps are involved: (1) crushing the attapulgite-associated gypsum and then sieving it, crushing the material on the sieve again until it is completely sieved, and then dehydrating the material under the sieve at a constant temperature to obtain powdered associated gypsum; (2) adding powdered associated gypsum to a mixer and adding water, then spraying a crystal-changing agent on the powdered associated gypsum while stirring, adjusting the pH to 4-8 after spraying the crystal-changing agent, adding an activator and continuing to stir evenly; (3) The crystallized material is dehydrated and dried, and then mixed with silicon dioxide and ground to obtain α-type high-strength gypsum.

2. The method for preparing α-type high-strength gypsum from powdered attapulgite-associated gypsum according to claim 1, characterized in that: The attapulgite associated gypsum in step (1) is crushed and sieved to a particle size of 0.2-2 mm.

3. The method for preparing α-type high-strength gypsum from powdered attapulgite-associated gypsum according to claim 1, characterized in that: The constant temperature dehydration temperature in step (1) is 140-160° C., the dehydration time is 60-150 min, and the crystal water content of the powdered associated gypsum after dehydration is 3-10%.

4. The method for preparing α-type high-strength gypsum from powdered attapulgite-associated gypsum according to claim 1, characterized in that: The crystal-transforming agent in step (2) is a composite crystal-transforming agent of aluminum sulfate, ethylenediaminetetraacetic acid and sodium citrate; the mass ratio of aluminum sulfate, ethylenediaminetetraacetic acid and sodium citrate in the crystal-transforming agent is 1:1-1.5:1-1.5; The activator is a mixture of sodium silicate and triisoalkanolamine, and the mass ratio of sodium silicate to triisoalkanolamine in the activator is 1:0.2-0.

35.

5. The method for preparing α-type high-strength gypsum from powdered attapulgite-associated gypsum according to claim 1, characterized in that: The amount of water added in step (2) is 10-20% of the mass of the powdered associated gypsum; The dosage of the crystallization agent is 0.2-0.6% of the mass of the powdered associated gypsum; The dosage of the activator is 0.5-1% of the mass of the powdered associated gypsum.

6. The method for preparing α-type high-strength gypsum from powdered attapulgite-associated gypsum according to claim 1, characterized in that: When the crystal-changing agent is sprayed in step (2), saturated water vapor is also introduced.

7. A method for preparing α-type high-strength gypsum from powdered attapulgite-associated gypsum according to claim 6, characterized in that: Saturated water vapor was introduced until the pressure inside the reactor reached 0.5-0.8 MPa.

8. The method for preparing α-type high-strength gypsum from powdered attapulgite-associated gypsum according to claim 1, characterized in that: The stirring rate in step (2) is 150-250 r / min, and each stirring time is 2-4 h.

9. The method for preparing α-type high-strength gypsum from powdered attapulgite-associated gypsum according to claim 1, characterized in that: The dehydration and drying temperature in step (3) is 140-160° C., the dehydration and drying time is 60-150 min, and the crystal water content of the powder after dehydration and drying is 5-7%.

10. The method for preparing α-type high-strength gypsum from powdered attapulgite-associated gypsum according to claim 1, characterized in that: In step (3), the mass ratio of the crystallized material to silicon dioxide is 1:0.05-0.15.